Physical, Sensory and Chemical Evaluation of Cooked Spaghetti - Martinez, Cristina Susana (2007)
The objectives of this research were to estimate the ability of chemical analysis, cooking properties, sensory evaluation and instrumental texture assays as descriptive quality parameters, and to evaluate the association between sensory and instrumental measurements on commercial pasta samples. Five commercial samples, Com1 to Com5, were analyzed. Moisture, protein and ash contents were determined from raw materials, while cooking loss, water absorption and leached amylose were measured in cooked samples. Color parameters ( L*, a* and b*) were determined spectrophotometrically and color scores were calculated from raw and cooked samples. Three instrumental texture assays by a texture analyzer (TA‐xT2i) and seven sensory parameters were evaluated. Chemical analysis, cooking properties, sensory evaluation and texture measurement were found to be sensitive quality parameters. From the analysis of the results, Com1 showed the best quality. A significant relationship between the sensory and instrumental measurements according to Pearson correlation and the principal component analysis was also observed.